Gates’ Interferometer as Fringe Projection System for Recovering 3d Shapes - Cordero-Carrasco, R; Leon-Rodriguez, M; Rayas, J (Springer New York LLC, 2017)
3D shape recovery systems, based on structured light projection, allow recovering three-dimensional shape from complex opaque surfaces. Particularly, when a fringe pattern with sinusoidal profile is projected on a surface and algorithms for recovering optical phase are performed for its demodulation, sub-micrometer resolutions can be obtained. The resolution is closely related to the angle formed by the axis system of projection and the observation direction; other important parameters are the local gradient of the sinusoidal profile Projected and the bit depth of the digital camera used to capture the deformed patterns. In this work, the projected sinusoidal fringe pattern is generated by a Gates’ interferometer where an expanded and collimated laser beam is impinged onto a non-polarizing cube beam splitter (parallel to the splitter coating). Internal reflections and refractions of the laser beam passing through the cube generate the interference fringes that are projected over the test object. The Fast Fourier Transform, FFT, technique and a simple phase unwrapping method are used for demodulation of registered fringe patterns. Results of the three-dimensional surface of a coin that has a relief of about 150 pm with a theoretical axial resolution varying from 0.1 to 7 are presented. © Springer International Publishing Switzerland 2017.